Radiometric measurement of forage quantity - R.C. Cochran; G. Towne; K. C. Olson (Kansas Agricultural Experiment Station Research Reports, 1995)
A 16-band multispectral radiometer (MSR) was used to measure the amount of forage biomass present on several dates in native tallgrass prairie pastures during the 1992 to 1994 growing seasons. Reflectance data collected with the MSR were used a s inputs for a neural network computer program. The neural network used the reflectance data to predict forage biomass. Biomass estimates made with the MSR were found to predict actual biomass, as measured by hand-clipping, across all plant growth stages with an error of approximately 6%. Radiometric determination of biomass is a reliable alternative to hand-clipping and can be accomplished in much less time.
Keywords: Cattlemen' s Day; 1995; Kansas Agricultural Experiment Station contribution; no. 95-357-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 727; Beef; Multispectral radiometer; Biomass; Forage; Neural network